Diagnostics of the formation of the graphic competence of future engineers-educators in the field of digital technologies - Koliasa, Pavlo Ivanovych (Journal of Education, Health and Sport, 2021)
The article analyses the scientific literature on the study of the problem of diagnosing the formation of graphic competence of future engineers-teachers in the field of digital technologies. Based on the analysis, the criteria for the formation of components of graphic competence (value-motivational, activity criteria, personal-creative and communicative-organizational criteria) are determined. An important aspect of the study is to determine the levels of graphic competence of future engineers-educators in the field of digital technologies, which we defined as: intuitive, reproductive, exploratory and creative, determined by the criteria and indicators of certain components